The role of FOMO and mindfulness in the relationship between mobile phone dependence and sleep quality among Chinese youth: a mediating and moderating analysis - Xie, Fen; Li, Mengyu (Frontiers in Psychology, 2025)
IntroductionAddressing the impact of problematic mobile phone use on sleep quality has become a topic of concern for researchers, but the underlying mechanisms and effective intervention strategies remain under explored.MethodsThe aim of this study was to investigate the effects of cell phone dependence on sleep quality, examining the role of FOMO (fear of missing out) as a mediator and mindfulness as a moderator. A total of 529 participants under 35 years were recruited to complete the survey. The research hypothesis was tested using Model 4 and Model 8 from the PROCESS macro in SPSS.ResultsFindings revealed that mobile phone dependence directly impairs sleep quality and indirectly exacerbates sleep disturbances through FOMO. Individual mindfulness traits mitigated the direct adverse effect of phone dependence on sleep quality, negatively moderated the relationship between phone dependence and FOMO.DiscussionThis study expanded the Media System Dependency Theory by introducing a dual-mechanism model of “psychological mediation + individual difference moderation”, and examined the moderating role of trait mindfulness within the Chinese cultural context. It is recommended that schools and enterprises incorporate mindfulness training into digital health curricula or daily training programs.